Editorial charters and newsroom councils in media corporations: a view from the perspective of corporate social responsibility (Communication & Society, 2015)
Editorial charters and professional representation groups in media corporations are major self-regulatory tools often cited in the Spanish literature on journalism ethics and deontology, yet many corporations lack them and they are largely invisible to the public with only a few exceptions, such as the Newsroom Council of the Spanish public national television network TVE. This limited implementation contrasts with the increasing number of media corporations that have adopted corporate social responsibility (CSR) policies that should take into account the expectations of journalists as internal stakeholders. The present study examines the relationships between editorial management and CSR management as a possible approach to integrating corporate governance and news governance in media corporations. The study is based on in-depth interviews of members of newsroom councils in Spanish media companies. Discourse analysis of these interviews indicates that journalists in media organizations do not consider that their companies’ CSR policies take into account their professional expectations, in the sense that journalists in these corporations do not perceive news governance and CSR management to be aligned. At the same time, the precarious labor market has led many journalists to stand up less to their employers on questions related to journalism standards. Nevertheless, many newsroom councils are effective at communicating complaints, violations and recommendations to corporate governance bodies.